(untitled) (Research, Society and Development, 2022)
This study aims to analyze breast cancer mortality rates and trends in women from breast cancer in Brazil and regions, from 2005 to 2019. This is an ecological, time-series study. Breast cancer mortality rates in female patients in Brazil from 2005 to 2019 were analyzed. Data were obtained by consulting the Online Atlas of Cancer Mortality, made available by the National Cancer Institute José Alencar Gomes da Silva (INCA) on the website of the Informatics Department of the Unified Health System (DATASUS). Data are presented descriptively and through tables. Statistical analysis was performed using the Statistical Package for Social Sciences (SPSS), version 15.0. The level of statistical significance adopted was 5%. The Southeast and South regions had the highest adjusted mortality rates, and the North region had the lowest rates. Rates increased with increasing age. A significant increase in mortality was observed for Brazil and all regions, during the years surveyed. The need for preventive measures for risk factors for breast cancer is emphasized, as well as specific social and health policies for the control of breast cancer in Brazil and reduce mortality.